Diagnostic challenges and treatment approaches for Clostridioides difficile infection in IBD patients - Ali, Asghar; AlHussaini, Khalid I. (Frontiers in Microbiology, 2026)
BackgroundClostridioides difficile infection (CDI) poses a major clinical challenge in patients with inflammatory bowel disease (IBD) due to overlapping symptoms, diagnostic complexities, and distinct therapeutic considerations. The interaction between CDI and IBD involves disrupted gut microbiota, immune dysregulation, and disease-specific risk factors.MethodsThis review critically examines the current evidence on the diagnosis and management of CDI in patients with IBD. Literature sources discussing diagnostic methodologies, therapeutic strategies, and preventive interventions were analyzed, with a focus on recent advances and their clinical applicability.ResultsDiagnosing CDI in IBD remains difficult due to similar clinical presentations between infectious colitis and IBD flares, alongside limitations of stool assays, molecular tests, and endoscopic evaluations. Emerging diagnostic tools may enhance the accuracy and timeliness of detection. Standard therapies, antibiotics, and fecal microbiota transplantation (FMT) remain essential; however, their application requires individualization, taking into account immunosuppressive therapy, drug interactions, and the risk of recurrence. Treatment outcomes are further influenced by disease severity and patterns of antimicrobial resistance. Preventive strategies, including antimicrobial stewardship, probiotics, and vaccination, may help reduce the incidence of CDI among patients with IBD.ConclusionCDI in IBD necessitates a personalized management approach that incorporates accurate diagnostics, targeted therapy, and preventive measures. Despite therapeutic advances, significant knowledge gaps persist regarding host microbiome interactions and the optimization of individualized treatment. Future research should focus on improving diagnostic precision and developing personalized medicine strategies to enhance outcomes for IBD patients affected by CDI.